Minocycline Reduces Hypothalamic Microglia Activation and Improves Metabolic Dysfunction in High Fat Diet-Induced Obese Mice - Coker, Caitlin R.; White, Melissa; Singal, Aneesh; Bingaman, Sarah S.; Paul, Anirban; Arnold, Amy C.; Silberman, Yuval (Frontiers in Physiology, 2022)
Obesity is associated with insulin resistance, glucose intolerance, inflammation, and altered neuronal activity in brain regions controlling metabolic functions including food intake, energy expenditure, and glucose homeostasis, such as the hypothalamus. In this study, we tested the hypothesis that inhibiting inflammation with minocycline could reduce adverse metabolic consequences associated with high-fat diet (HFD)-induced obesity in mice and sought to determine if metabolic improvements were associated with reduced hypothalamic microglia activity. Male C57Bl/6J mice were placed on 60% HFD for 12 weeks, with minocycline (40 mg/kg, p.o.) or normal tap water given during the last 6 weeks of diet. Age-matched mice maintained on control diet were used as an additional comparator group. Metabolic function was assessed during the last week of treatment. Ramified (resting) and non-ramified (active) microglia were quantified in the hypothalamus following immunohistochemical staining of ionized calcium-binding adaptor 1 (Iba-1) and further assessed by RNAseq. In HFD fed mice, minocycline attenuated body mass and adiposity without altering food intake suggesting enhanced energy expenditure. Minocycline also attenuated hyperinsulinemia and improved insulin sensitivity in HFD mice. Increased microglial activation and autophagy gene network changes were observed in the paraventricular nucleus (PVN) of the hypothalamus of HFD mice, which was prevented by minocycline treatment. Contrary to PVN findings, there were no significant effects of either HFD or minocycline on microglia activation in the hypothalamic arcuate nucleus or central amygdala. Together, these findings suggest that minocycline improves HFD-induced weight gain and insulin resistance in part by reducing inflammatory processes in the PVN, a key hypothalamic region regulating metabolic function.